Elementary preservice teachers’ knowledge, perceptions and attitudes towards fractions: A mixed-analysis - Rosli, Roslinda; Goldsby, Dianne; Onwuegbuzie, Anthony J.; Capraro, Mary Margaret; Capraro, Robert M.; Gonzalez, Elsa Gonzalez Y. (Journal on Mathematics Education, 2020)
Previous research has shown knowledge, perceptions, and attitudes are essential factors during mathematics classroom instruction. The current study examined the effects of a 3-week fraction instructional unit using concrete models, problem-solving, and problem-posing to improve elementary preservice teachers’ knowledge, perceptions and attitudes towards fractions. A quasi-experiment design was implemented to gather data via closed-ended, open-ended, and essay tasks from a convenience sampling of 71 female elementary preservice teachers during pre- and post-assessments. The study discovered that the select preservice teachers were weak in the content knowledge specifically on unit-whole, part-whole, equivalent area, arithmetic operations, and ordering fractional values. In contrast, the incorporation of concrete models, problem-solving and problem- posing was effective in improving the preservice teachers’ level of pedagogical content knowledge, perceptions and attitudes towards fractions. Implications of the results and suggestions are discussed.